Diseases of the nervous system: patients' aetiological beliefs. Issue 4 (16th March 2005) - Croquelois, A; Assal, G; Annoni, J-M; Staub, F; Gronchi, A; Bruggimann, L; Dieguez, S; Bogousslavsky, J
Abstract : Background: Patients' opinions about the aetiology of their disease and the implications for compliance have not been well documented at this time. Objective: To investigate prospectively aetiological beliefs of a cohort of neurological inpatients. Methods: Within two days of admission, patients orally answered a short questionnaire regarding their beliefs about the aetiology of their disease and the possible influence of psychological factors, stress, fatigue, excessive work or other activities, poor lifestyle, conflict with another person, a tragic event, chance, and destiny. Results: Of the 342 patients who participated in the study, 49% spontaneously said that they had no idea of what could have caused their disease, 15% gave a congruent medical explanation, 11% mentioned stress and fatigue as a precipitating factor, and 6% evoked a non-congruent medical explanation. Thirty six per cent thought that psychological factors had triggered their disease; such factors being blamed by a higher proportion of young patients and patients with chronic central nervous system diseases. The triggering factors most often blamed were stress (48%, especially by patients with headache), fatigue (51%), chance (54%), and destiny (43%). Conclusions: Patients' aetiological beliefs only partially concur with medical opinion and this may influence compliance with treatment. This statement should be explored and confirmed by further studies—for example, in cerebrovascular risk factor follow up.